Media Audio Visual sebagai Sarana Edukasi untuk Meningkatkan Pengetahuan WUS tentang Metode Kontrasepsi IUD - Lubis, Rospita Diansari; Lisviarose, Lisviarose; Nadia, Fatma; Aifa, Wira Ekdeni (Journal of Telenursing (JOTING), 2026)
This study aimed to examine the effect of audiovisual media on the knowledge of women of reproductive age regarding intrauterine device (IUD) contraceptive methods. The research employed a pre experimental design with a one-group pretest–posttest approach. The results showed a p-value of 0.001 (< 0.05), indicating a statistically significant difference in the level of knowledge of women of reproductive age before and after the intervention using audiovisual media. In conclusion, there was a significant difference in the level of knowledge before and after the provision of the audiovisual media intervention. It is expected that the findings of this study can support the use of audiovisual media as a health education tool in community counseling activities at Puskesmas Rakit Kulim in 2025.   Keywords : IUD, Knowledge Of Women Of Childbearing Age, Audiovisual Media